СЕГМЕНТ СПІЛКУВАННЯ У СТРУКТУРІ ПЕДАГОГІЧНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ВЧИТЕЛЯ (Pedagogy of Higher and Secondary Education, 2012)
У статті автор дає обґрунтування сегменту спілкування в структурі педагогічної культури майбутнього вчителя, багатоплановому процесі організації, встановленні і розвитку контактів, взаєморозумінні і взаємодії між майбутнім учителем і учнем.Ключові слова: сегмент спілкування, педагогічна культура.In the given article the author presents the basic structural laws of the pedagogical culture of a teacher to be and their influence on the planning, organizing and developing contacts between future teachers and pupils  in the spirit of improving their further mutual understanding and cooperation.Key words: structural laws, pedagogical culture.
Keywords: structural laws; pedagogical culture